Pengaruh Kepemimpinan Kepala Sekolah dan Supervisi Akademik terhadap Kinerja Guru di Sekolah Dasar Negeri Kecamatan Sagulung - Hanna Lisa Siahaan (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Teachers as professionals at the level of formal education are appointed in accordance with statutory regulations. The position of teachers as professionals serves to improve the dignity and the role of teachers as learning agents serves to improve the quality of national education. The formulation of the problem in this study is whether the principal's leadership and academic supervision partially and simultaneously affect the performance of public elementary school teachers in Sagulung District. The purpose of this study is to determine and analyze the influence of the principal's leadership and academic supervision on teacher performance. The design of this study is a causality research design by considering the influence of the variables of the principal's leadership and academic supervision on teacher performance. The type of data used is quantitative data. The study was conducted on public elementary school teachers in Sagulung District with a population of 502 people and a sample of 223 people. The sample was taken by using purposive sampling technique, which does not provide equal opportunities to be respondents but based on certain criteria. The independent variables in this study are the Principal's Leadership and Academic Supervision, while the dependent variable is Teacher Performance. Variable measurements were carried out by using a Likert scale. Data analysis was carried out by using Statistical Product and Service Solutions (SPSS). Data analysis was conducted by applying Descriptive Analysis, Classical Assumption Test, and Hypothesis Testing. Based on the results of the analysis the first hypothesis has a significant influence of the principal's leadership (X1) on teacher performance (Y). The second hypothesis has no significant effect of academic supervision (X2) on teacher performance (Y). The third hypothesis has a significant effect of principal leadership (X1) and academic supervision (X2) together on teacher performance (Y).